Implementing Blended Learning to Promote Sustainable Teaching and Learning Process in Writing Class - Puspita, Nurul; Hasyim, Umar Alfaruq A (English Education: Jurnal Tadris Bahasa Inggris, 2019)
Teaching writing in the era of industrial revolution 4.0 is very challenging and interesting. This era encourages both lecturer and the student utilizing informatics technology in teaching and learning process. Since, the process of teaching writing needs more time, the classroom activities do not accomodate the whole processes such as, planning, drafting and revising. Therefore, it needs solution to sustain the teaching and learning process not only in the classroom but also outside the classroom. Blending Google Classroom and classroom activities is one of solutions to lead sustainable teaching and learning process, especially in writing class. Thus, this research aims at describing the implementation of that blended learning in teaching and learning writing. It is descriptive qualitative research that capturing the lecturer and students of English department UIN RIL Lampung in implementing blended learning. Finally, this research found that blending Google Classroom and classroom activities could make the process of teaching writing carried out completely, continuously  and well-controlled.